RISK MANAGEMENT PLANNING PROCUREMENT PROJECT IT USE ISO 31000 IN PT.PELABUHAN INDONESIA III - Donny Bustan Fauzi; Haryanto Tanuwijaya; Sri Hariani Eko Wulandari (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT. Pelabuhan Indonesia III (Persero) is a state-owned company that runs the business as a provider of port service facilities (traffic activities of vessels and goods) in the whole territory of the port management. Traffic from ship visits in 2013 grew. , 46% from 2012. This increase pushed the management to afford competitive by developing and building an infrastructure that can support the smooth business operations. In doing development and infrastructure development are the risks that may occur with regard to cost, time and quality of the project, where the company should be able to manage the risk of the project management of information technology, however PT Pelabuhan Indonesia III does not currently have Standard Operation and Procedure ( SOP) to identify risks in any information technology project being run. The absence of standard SOP in identifying the risks of project procurement lead Sub-Directorate of Risk Management and Quality have difficulty in overcoming the risk that the information technology project is being executed.The purpose of this research is to design a risk management document that projects that focus on procurement refers to the ISO 31000 framework in the form of Standard Operation Procedure (SOP) and Work Instructions (IK) is used to manage the risk of the procurement of information technology projects. Risk management planning procurement of information technology projects generate Standadrd Operation Procedure Risk Management and Work Instructions that the company needs to conduct risk identification procurement of information technology projects